Next-generation mobile and pervasive healthcare solutions - Machado, José Manuel; Abelha, António, 1964-; Santos, Manuel Filipe; Portela, Filipe (Advances in medical technologies and clinical practice book series., 2018)
"This book provides decision support anywhere and anytime to acute and long term health care taking as based pervasive or mobile computing. It promotes the cross-fertilization of health informatics information and knowledge across professional and geographical boundaries, serving as the catalyst for ubiquitous worldwide health information infrastructures for patient care and health research"--